Kesalahan Siswa Menyelesaikan Soal Pola Bilangan, Barisan, dan Deret Tipe HOTS Berdasarkan Teori Newman Ditinjau dari Gender - Siagian, Qania Agustika; Herman, Tatang; Darhim, Darhim; Khairunnisa, Khairunnisa (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
This study aims to analyze the errors of students with HOTS abilities at high, medium and low levels and identify student errors in solving HOTS (Higher Order Thinking Skill) type questions in terms of gender. This type of research is qualitative with a case study approach. The research subjects were selected 3 male students and 3 female students, each of which the HOTS ability level was high, medium and low consisting of 2 students. Data collection techniques used HOTS-type tests and interviews. The analytical framework was developed based on Newman's theory of error categories. The data obtained were tested for validity through credibility, transferability, dependability, and confirmability tests. The results showed several differences in the types and percentages of errors made by male and female subjects in solving HOTS-type questions. The biggest mistakes made by both genders in the material of number patterns, sequences, and series are misunderstandings of 33.33%, followed by errors in determining the final answer of 23.02%, transformation errors of 22.22%, errors in the completion process of 20.63%, and finally, reading errors of 0.79%. It can be seen that the female gender makes more mistakes by 57.14% compared to the male gender by 41.86%.